2008
DOI: 10.1016/j.homp.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Delayed luminescence of high homeopathic potencies on sugar globuli

Abstract: Delayed luminescence signals of Arg.met. CMf (100Mf), Canth. CMf, Bov. CMf absorbed onto sugar globuli was observed by exciting them at their known resonance frequency of 2.060 MHz. Arn. CMf also showed delayed luminescence when excited at 2.060 MHz and at 1.828 MHz. Alc. LMK (50MK) could not be excited by 2.060 MHz and showed properties of control globuli. Canth. LMK could not be excited at 2.006 MHz. The delayed luminescence signals were characterized by the coefficient B(2) typical of the delayed luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 6 publications
4
35
0
Order By: Relevance
“…In 2016 magnetic photons, monopoles + and -, had been detected at the CERN Institute in Geneva [38,39]. Finally, this is a confirmation of Lenger's findings [32][33][34].…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…In 2016 magnetic photons, monopoles + and -, had been detected at the CERN Institute in Geneva [38,39]. Finally, this is a confirmation of Lenger's findings [32][33][34].…”
Section: Resultssupporting
confidence: 74%
“…DL [33,34]: This second method confirms again that photons of homeopathic remedies could be separated from the carrier substance, saccharose or ethanol by their resonant frequency field. It is assumed that this field is the magnetic field because the trials with the Tesla-coils showed that the electric field did not react.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The experimental results indicate that "pure" water samples can retain specific information regarding a "donor" substance which can be quantitatively measured via thermoluminescence, delayed luminescence, excess heat-of-mixing/microcalorimetry, changes in pH and conductivity, alterations to FTIR spectra, enzymatic activity, and modulation of chemical, biochemical, and biological processes usually in accord with the donor substance. These experiments have been carried out with biological bioassays with dinoflagellates comparing succussed media, and modulation to Ca 2+ channel affinity by non-thermal microwave exposure, as well as investigating physico-chemical effects on purely chemical systems using ultra-high dilution of lithium chloride, sodium chloride, mercuric chloride, and mercuric iodide [155][156][157][158][159][160][161][162][163][164][165][166][167][168].…”
Section: Role Of Watermentioning
confidence: 99%